Realism and Illusion in Americans' Temporal Views of Their Life Satisfaction - Lachman, Margie E.; Röcke, Christina; Rosnick, Christopher; Ryff, Carol D. (Psychological Science, 2008)
We examined actual and perceived trajectories of change in life satisfaction in a national sample of 3,793 adults, ages 24 to 74 at baseline, who provided retrospective, present, and prospective ratings on two occasions 8 to 10 years apart. There was little actual change in satisfaction ratings, but there were age differences in anticipated change, with young adults expecting things to improve and older adults expecting decline. When we compared the actual (present) ratings with corresponding past or future ratings, older adults showed more temporal realism (retrospective and anticipatory ratings matched actual levels) than did young and middle-aged adults; in other words, young and middle-aged adults showed greater illusion (retrospective and prospective ratings overestimated or underestimated actual levels). At all ages, however, temporal realism was associated with more adaptive current functioning than was illusion. We discuss these findings from a life-span developmental perspective on motivational shifts from growth to maintenance and consider the implications of accuracy in evaluating the past and future.